A New Activated Carbon for CO Capture from Coal-Fired Boiler Flue Gas - J. Don Carruthers; Melissa A. Petruska; Gopala Krishnan; Marc Hornbostel; Jianer Bao (Adsorption Science & Technology)
With the current environmental interest in controlling greenhouse gases, there is a new focus on materials that can discriminate between gas molecules by capturing those gases that must be curtailed and releasing those that pose no adverse effects to the atmosphere. Although zeolites can be applied to such tasks, molecular sieve (MS) carbons have an additional advantage in their ability to both adsorb and desorb molecules cyclically with comparatively little energy demand. ATMI's BrightBlack™ MS carbons have been extensively characterized using a variety of techniques and modified for the task of selectively adsorbing CO 2 from a synthetic flue gas in a laboratory and a pilot plant falling-bed adsorber system. The integrated falling-bed adsorber system was then moved to a field test location to capture CO 2 from flue gas from a coal-fired stoker boiler. In a 7000-cycle test, the carbon captured CO 2 at 90% efficiency, generating product CO 2 gas with purity greater than 95%.